Preserve the existence of balala’ tamakng tradition of dayak ethnic to maintain the national identity of indonesia - Iwan Ramadhan; Imran Imran; Muhammad Agus Hardiansyah; Cary Chappel; Haris Firmansyah (Jurnal Pendidikan PKN (Pancasila dan Kewarganegaraan), 2023)
The Balala' Tamakng tradition is a tradition of abstinence that is still believed and carried out by the Dayak ethnic community in Sungai Ambawang District, Kubu Raya Regency. This study aims to determine the procession of the Balala' Tamakng tradition, the symbolic meaning of the Balala' Tamakng tradition and efforts to maintain the Balala' Tamakng tradition in the era of globalization in an effort to maintain national identity. The high flow of globalization, indirectly, has gradually faded the traditions of today's traditional society. This research seeks to discover the efforts of the Dayak ethnic community in Sungai Ambawang District in preserving the Balala' Tamakng tradition in maintaining national identity amidst the influence of globalization. The research method used is descriptive research using a qualitative approach. The data collection technique that will be used is the process of observation, in-depth interviews, and documentation. The research results in a state that the Balala' Tamakng tradition is carried out through the process of the ritual. As for the meaning or meaning of the Balala' Tamakng tradition, it is abstinence for a full day with the condition that you are not allowed to set foot out of the house, not shout or make noise in the house. In this era of globalization, efforts to maintain the Balala' Tamakng tradition are made by strengthening national identity and by sharing these ritual activities through social media